In vitro antimicrobial activity of auxiliary chemical substances and natural extracts on Candida albicans and Enterococcus faecalis in root canals - Marcia Carneiro Valera; Lilian Eiko Maekawa; Luciane Dias de Oliveira; Antonio Olavo Cardoso Jorge; Érika Shygei; Cláudio Antonio Talge Carvalho (University of São Paulo, 2013)
Objective: The aim of this study was to evaluate the antimicrobial activity of auxiliary chemical substances and natural extracts on Candida albicans and Enterococcus faecalis inoculated in root canals. Material and Methods: Seventy-two human tooth roots were contaminated with C. albicans and E. faecalis for 21 days. The groups were divided according to the auxiliary chemical substance into: G1) 2.5% sodium hypochlorite (NaOCl), G2) 2% chlorhexidine gel (CHX), G3) castor oil, G4) glycolic Aloe vera extract, G5) glycolic ginger extract, and G6) sterile saline (control). The samples of the root canal were collected at different intervals: confirmation collection, at 21 days after contamination; 1st collection, after instrumentation; and 2nd collection, seven days after instrumentation. Microbiological samples were grown in culture medium and incubated at 37°C for 48 hours. Results: The results were submitted to the Kruskal-Wallis and Dunn (5%) statistical tests. NaOCl and CHX completely eliminated the microorganisms of the root canals. Castor oil and ginger significantly reduced the number of CFU of the tested bacteria. Reduction of CFU/mL at the 1st and 2nd collections for groups G1, G2, G3 and G4 was greater in comparison to groups G5 and G6. Conclusion: It was concluded that 2.5% sodium hypochlorite and 2% chlorhexidine gel were more effective in eliminating C. albicans and E. faecalis, followed by the castor oil and glycolic ginger extract. The Aloe vera extract showed no antimicrobial activity.